Effectiveness Leadership of Principal - Rudolf Kempa; Marthen Ulorlo; Izaak Hendrik Wenno (International Journal of Evaluation and Research in Education (IJERE), 2017)
Effective principal leadership is a leadership that can foster cooperative efforts and maintain an ideal working climate in schools. The purpose of this research is to know the effectiveness leadership of the principal of the 2nd State Junior High School of Ambon, with qualitative approach. Data sources include school principals, vice principals, heads of administration, heads of affairs, library coordinators, teacher subject coordinators, counselors coordinators, and school supervisors. Data collection techniques through Focus Group Discussion, Interview, Observation, and documentation study. The analysis technique used is descriptive narrative. The results concluded that the leadership style of principal in the 2nd State Junior High School of Ambon has not been effective.